The Probiotication of a Lychee Beverage with Saccharomyces boulardii: An Alternative to Dairy-Based Probiotic Products - Marcela Moreira Terhaag; Otávio Akira Sakai; Fabiana Ruiz; Sandra Garcia; Fernando Rodrigo Bertusso; Sandra Helena Prudêncio (Foods)
Probiotic vegetable-based beverages, such as lychee, can be rich in nutrients, free of cholesterol and lactose, and also have few allergenic components. Saccharomyces boulardii is an alternative to make lychee juice a probiotic beverage. This work aimed to develop probiotic lychee beverage (LB) using S. boulardii by evaluating the effect of refrigerated storage on cell viability, physicochemical characteristics, and acceptance. LB supplemented with S. boulardii was fermented (24 h/30 °C), supplemented with sucrose (4–12 °Brix), and refrigerated (up to 28 days/4 °C). The yeast viability, total soluble solid (TSS) and, ethanol content, pH, total phenolic compounds (TPC), and antioxidant activity (AA) levels were evaluated over 28 days of storage. Also, the profiles of sugars, organic acids, and phenolic were determined via chromatographic analysis. The sensory acceptance of the probiotic beverage was evaluated. Higher sucrose levels (12 °Brix) resulted in greater yeast viability (6.9 log CFU/mL) on the 21st day of storage and superior TPC (153 µmol TEAC/mL) and ethanol levels (8.7%). Storage reduced the TPC, AA, and TSS. LB supplemented with sucrose to 12 °Brix, probioticated by S. boulardii, and stored for 21 days became accepted by the consumer and presented an adequate physicochemical profile with probiotic potential. The probiotication of lychee beverage is an alternative to dairy-based probiotic beverages.